[Kulintang exhibition [videorecording] - Philippines. National Commission for Culture and the Arts. (Manila NCCA, 1995)
A musical exhibition of Kulintang playing.
VHS.
Keywords: Kulintang (Musical instrument); Musical instruments, Maranao